A prospect of cost-effective handling and transportation of graphene oxides: folding and redispersion of graphene oxide microsheets. (17th August 2021) - Chang, Chao-Wen; Zamani, Somayeh; Smilgies, Detlef M; Seo, Honguk; Park, Sangjoon; Kang, Taechung; Lim, Ae Ran; Joo, Yong Lak
Abstract: Controlling the assembly of 2D materials such as graphene oxides (GO) has a significant impact on their properties and performance. One of the critical issues on the processing and handling of GO is that they need to be in dilution solution (0.5 to 2.5 wt%) to maintain their high degree of exfoliation and dispersion. As a result, the shipment of GO in large quantity involves a huge volume of solvent (water) and thus the transportation costs for large sales volume would become extremely high. Through cross-sectional scanning electron microscopy and polarized optical microscopy together with x-ray diffraction and small-angle x-ray scattering studies, we demonstrated that the assembly and structure of GO microsheets can be preserved without restacking, when assembled GO via water-based wet spinning are re-dispersed into solution. A couple of alkyl ammonium bromides, CTAB and TBAB, as well as NaOH, were examined as coagulants and the resulting fibers were redispersed in an aqueous solution. The redispersed solution of fibers that were wet-spun into the commonly used CTAB and TBAB coagulation baths, maintained their physico-chemical properties (similar to the original GO dispersion) however, did not reveal preservation of liquid crystallinity. Meanwhile, the redispersed fibers that were initially spun into NaOH coagulation bath were able to maintain their liquid crystallinity if the lateral size of the GO sheets was large. Based on these findings, a cost-effective solid handling approach is devised which involves (i) processing GO microsheets in solution into folded layers in solid-state, (ii) transporting assembled GO to the customers, and (iii) redispersion of folded GO into a solution for their use. The proposed solid handling of GO followed by redispersion into solution can greatly reduce the transportation costs of graphene oxide materials by reducing the transportation volume by more than 90%.